Approach to the Engineering Education applying NASA Systems Engineering - Masaaki Komatsu; Hideaki Aburatani; Sanit Teawhim (2022 7th International Conference on Business and Industrial Research (ICBIR), 2022)
KOSEN-KMITL, the first Japanese style KOSEN in Thailand, was established on May 2019 in King Mongkut’s Institute of Technology Ladkrabang (KMITL). KOSENKMITL is an Engineering, Technology, and Innovation work force development project, to support, raise the investment and increase the industrial capacity of the Thai industry region. At the establishment of this college, we need to design, develop, and implement all the engineering related subject starting from zero. We have no good reference to establish the Engineering Design course. The author of this paper, who had engaged in NASA/JAXA International Space Station for a long time, proposed to apply the “NASA Systems Engineering Handbook” to the Engineering Design Course in KOSEN-KMIT. NASA had developed and published their “NASA Systems Engineering Handbook” in 2007 and NASA goes public it worldwide under the NASA Science and Technical Information (STI) program. This NASA Systems Engineering Handbook is expected to provide the technical guidance and information on systems engineering that will be beneficial to the aerospace community and other related industrial community. On the other hand, this handbook would be a good textbook for the University and college students who are in the engineering course and study the engineering design, system engineering, and other engineering related subject. We also apply this NASA System Engineering Handbook to the case “Introduction to Engineering Design,” “Introduction to Design Approach,” “Reverse Engineering” for the 1 st and 2 nd grade students and “PBL” for the 3 rd grade students. As the result, students can learn the project life cycle process from concept study to critical/final design and apply these engineering approach to their projects for the 1st grade, 2 nd grade, and 3 rd grade students. It would be very important to develop the skill and bring up the engineering mind-set as early stage in the engineering course for the younger students. The objective in this paper, we would clarify the result in efficiency and availability for this approach and then we could validate that this approach is very effective for the engineering course and can apply as an early engineering education.
Keywords: Technology Assessment and Management; Systems Engineering Methodologies and Applications; Engineering Education and Pedagogy